2019
DOI: 10.1038/s41559-019-0831-4
|View full text |Cite
|
Sign up to set email alerts
|

The evolutionary ecology of circadian rhythms in infection

Abstract: Biological rhythms coordinate organisms' activities with daily rhythms in the environment. For parasites, this includes rhythms in both the external abiotic environment and the within-host biotic environment. Hosts exhibit rhythms in behaviours and physiologies, including immune responses, and parasites exhibit rhythms in traits underpinning virulence and transmission. Yet, the evolutionary and ecological drivers of rhythms in traits underpinning host defence and parasite offence are largely unknown. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
69
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 106 publications
1
69
0
Order By: Relevance
“…Here we identified an enrichment of DEGs associated with circadian rhythm. Within host-parasite interactions, parasites must contend with and can affect host circadian rhythms (Reece et al, 2017;Westwood et al, 2019). This is best documented in parasites of medical importance, where symptoms of infection include irregular circadian rhythms, such as in the case of human infections by parasitic species, such as Plasmodium (Kwiatkowski and Greenwood, 1989) and Trypanosoma species (Rijo-Ferreira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Here we identified an enrichment of DEGs associated with circadian rhythm. Within host-parasite interactions, parasites must contend with and can affect host circadian rhythms (Reece et al, 2017;Westwood et al, 2019). This is best documented in parasites of medical importance, where symptoms of infection include irregular circadian rhythms, such as in the case of human infections by parasitic species, such as Plasmodium (Kwiatkowski and Greenwood, 1989) and Trypanosoma species (Rijo-Ferreira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…However, on the one hand it is important to consider not only the levels of proinflammatory cytokines, but also the presence of the first-responders in the blood, which can serve as a source of neutrophils and other myeloid cells during the acute phase, prior to the mobilization from their reservoirs in the head kidney. On the other hand, we should keep in perspective that pathogens like bacteria and parasites are also regulated by circadian rhythms [39][40][41], and they eventually manipulate the host rhythmicity for their own benefit [42,43] as viruses do as well [44]. Therefore, "when" a pathogen attacks a host, and how the host defend itself, is a fact regulated by an exquisite balance between the species involved.…”
Section: Discussionmentioning
confidence: 99%
“…The value of coordinating with daily cycles in, for example, light/dark and temperature in the abiotic environment has long been appreciated, and the importance for parasites of coordinating with rhythms experienced inside hosts and vectors (i.e. the biotic environment), is gaining increasing recognition [1-3]. For example, circadian rhythms in virulence enables the fungal pathogen Botrytis cinerea to cope with rhythmic immune defences in plant hosts [4, 5], circadian control of macrophage migration provides incoming Leishmania major parasites with more host cells to invade at dusk than dawn [6], and host clocks control the ability of herpes and hepatitis viruses to invade cells and to replicate within them [7, 8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has been suggested that the IDC schedule is entirely explained by circadian host immune responses killing certain IDC stages at certain times of day [23] or by only allowing access to a nutrient essential to a particular IDC stage at a certain time-of-day [24]. Alternatively, parasites may be able to, at least in part, schedule their IDC to avoid coinciding a vulnerable IDC stage with a dangerous time-of-day, or to maximally exploit a time-limited resource [3]. A foundation for explaining both why the IDC schedule benefits parasites and how it is controlled, requires discovering which of the myriad of host rhythms associated with the time-of-day of feeding are responsible for the IDC schedule.…”
Section: Introductionmentioning
confidence: 99%